An immunomodulatory bioink with hollow manganese silicate nanospheres for angiogenesis. (June 2021) - Wu, Jinfu.; Qin, Chen; Ma, Jingge; Zhang, Hongjian; Chang, Jiang; Mao, Lixia; Wu, Chengtie
Highlights: MS nanospheres could significantly enhance the expression of typical anti-inflammatory genes and stimulate macrophages into M2 phenotype. The immune microenvironment mediated by MS could activate angiogenesis-related factors of endothelial cells. The MS-containing bioinks held immunomodulatory properties for macrophages. The MS-based bioink could support the stability and viability of the scaffolds for even 21 days of culture. Abstract: Angiogenesis is critical for repairing vascularized tissues. Since the immune system plays vital roles in the processes of angiogenesis, the effects of immune environment should be fully considered when designing biomaterials. The scaffolds with beneficial immunomodulatory effects on angiogenesis are urgently needed for vascularized tissues regeneration. In this work, an immunomodulatory bioink was developed based on the bioactive manganese silicate (MS) nanospheres. The immunomodulatory effects of MS on macrophages were investigated, and the beneficial angiogenic effects of the MS-mediated immune environment on endothelial cells were studied. Furthermore, with the MS-containing bioinks, "macrophages-endothelial cells" co-culture scaffolds were printed via 3D bioprinting strategy. The MS-containing bioinks possessed robust printability and formability, and could stably support the viability of the cells even after 21 days of culture. This study puts forward a useful strategy for developing bioinks with immunomodulatory effects for promoting angiogenesis. It offers a potential solution for vascularized tissues regeneration through bioprinting multiple tissue cells in combination of nanomaterials-mediated immune environment. Graphical abstract: Manganese silicate (MS) nanospheres could significantly enhance the expression of typical anti-inflammatory genes and stimulate macrophages into M2 phenotype. The immune microenvironment mediated by MS could activate angiogenesis-related factors of endothelial cells. With the MS-based bioinks, "macrophages-endothelial cells" coculture scaffolds were printed via 3D bioprinting strategy. The MS-based bioink could support the stability and viability of the scaffolds for even 21 days of culture. Image, graphical abstract